Senolytic treatment reduces cell senescence and necroptosis in Sod1 knockout mice that is associated with reduced inflammation and hepatocellular carcinoma. Issue 8 (23rd July 2022) - Thadathil, Nidheesh; Selvarani, Ramasamy; Mohammed, Sabira; Nicklas, Evan H.; Tran, Albert L.; Kamal, Maria; Luo, Wenyi; Brown, Jacob L.; Lawrence, Marcus M.; Borowik, Agnieszka K.; Miller, Benjamin F.; Van Remmen, Holly; et al.
Abstract: The goal of this study was to test the role cellular senescence plays in the increased inflammation, chronic liver disease, and hepatocellular carcinoma seen in mice null for Cu/Zn‐Superoxide dismutase (Sod1KO). To inhibit senescence, wildtype (WT) and Sod1KO mice were given the senolytics, dasatinib, and quercetin (D + Q) at 6 months of age when the Sod1KO mice begin exhibiting signs of accelerated aging. Seven months of D + Q treatment reduced the expression of p16 in the livers of Sod1KO mice to WT levels and the expression of several senescence‐associated secretory phenotype factors (IL‐6, IL‐1β, CXCL‐1, and GDF‐15). D + Q treatment also reduced markers of inflammation in livers of the Sod1KO mice, for example, cytokines, chemokines, macrophage levels, and Kupffer cell clusters. D + Q treatment had no effect on various markers of liver fibrosis in the Sod1KO mice but reduced the expression of genes involved in liver cancer and dramatically reduced the incidence of hepatocellular carcinoma. Surprisingly, D + Q also reduced markers of necroptosis (phosphorylated and oligomerized MLKL) in the Sod1KO mice to WT levels. We also found that inhibiting necroptosis in the Sod1KO mice with necrostatin‐1s reduced the markers of cellular senescence (p16, p21, and p53). Our study suggests that an interaction occurs between cellular senescence and necroptosis in the liver of Sod1KO mice. We propose that these two cell fates interact through a positive feedback loop resulting in a cycle amplifying both cellular senescence and necroptosis leading to inflammaging and age‐associated pathology in the Sod1KO mice. Abstract : Senescence‐associated secretory phenotype factors produced by senescent cells induce cells to undergo necroptosis, and damage‐associated molecular patterns produced by cells undergoing necroptosis induce cell senescence produce a cycle amplifying both cell fates leading to inflammaging.